2021
DOI: 10.1093/ajh/hpab168
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability of Pressure-Corrected Arterial Stiffness Indices: Comparison of Pulse Wave Velocity, Cardio-Ankle Vascular Index (CAVI), and CAVI0

Abstract: BACKGROUND Pulse wave velocity (PWV) is blood pressure (BP) dependent, leading to the development of the BP-corrected metrics cardio-ankle vascular index (CAVI) and CAVI0. We aimed to assess risk prediction by heart-to-ankle PWV (haPWV), CAVI, and CAVI0 in a US population. METHODS We included 154 subjects (94.8% male; 47.7% African American) with and without heart failure (HF). Left and right haPWV, CAVI, and CAVI0 were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(62 reference statements)
0
6
0
1
Order By: Relevance
“…Our study moves from the assumption that CAVI is a valid estimate of arterial stiffening in older ages [25]. Although guidelines endorse the use of cfPWV as the gold standard for arterial stiffness evaluation [3], there has been increasing interest in CAVI and CAVI0 [26]. As compared to cfPWV, which is a particular measurement of the central aortic segments, CAVI is known to be representative of a wider proportion of the arterial tree, including both central and peripheral segments [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our study moves from the assumption that CAVI is a valid estimate of arterial stiffening in older ages [25]. Although guidelines endorse the use of cfPWV as the gold standard for arterial stiffness evaluation [3], there has been increasing interest in CAVI and CAVI0 [26]. As compared to cfPWV, which is a particular measurement of the central aortic segments, CAVI is known to be representative of a wider proportion of the arterial tree, including both central and peripheral segments [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the formula for estimating haPWV-relevant BP is incorrect, and there is no basis for the claim that the BP is almost P d . Also, they claim that the negative correlation with BP is because of high pulse pressure among the individuals with lower P d , who are supposed to have stiffer blood vessels [29]. However, a negative relationship is observed even in healthy people with pulse pressure less than 50 mmHg [34].…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of CAVI compared with the other two parameters identified in the present study seems to be inconsistent to the findings of Spronck et al . [29] compared the same three arterial stiffness parameters in 154 individuals. They reported that the predictive ability of the composite endpoint [death ( n = 21) and heart failure hospitalization ( n = 18)] showed a decreasing trend of haPWV to CAVI to CAVI 0 , and the investigators attributed these results to the increasing amount of BP correction of the parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable relationship between age and CAVI was previously demonstrated by Shirai et al [ 46 ], who described increased CAVI in elderly subjects as a possible expression of age-related arterial wall sclerosis. Although PVW-cf is still considered as the primary arterial stiffness evaluation technique for outcome prediction [ 47 ], CAVI could be also considered as a more reliable index in the elderly, due to its lower dependence from blood pressure [ 48 ].…”
Section: Discussionmentioning
confidence: 99%